Enhancement of Forced Convection Heat Transfer for SiO2 flow through Channel with Ribs at Constant Heat Flux (International Journal of Scientific Research and Management (IJSRM), 2018)
Numerical investigation of forced convective flow in a 2-dimensional microchannel. This investigation is analyzed with nanoparticles SiO2 and water as a base fluid studying the influence of turbulence model inside multi geometrical channel (Triangular, Trapezoidal, Semi-circular, and Rectangular) by using "Finite Volume Method (FVM)". The heat flux is applied on the lower wall of channel and the upper is insulated. The diameter of nanoparticles is 20 nm. The Reynolds number ranges are from 10000 to 30000 for ratio of groove width (B) to channel height (H) was used 0.75. The volume fractions range is between 1-4%. Triangular channel score higher Nusselt number and lower friction factor than other cases against Reynolds number. When the volume fraction was increase, the Nusselt number increased and friction factor decreased, this gives 4% has the optimal properties.